The effects of repeated fecal transplantation and activated charcoal treatment on gut dysbiosis induced by concurrent ceftriaxone administration in mice - Sarinya Kumpunya; Kornthara Kawang; Kraiwit Pollapong; Voraphoj Nilaratanakul (Scientific Reports)
Abstract Background: Antibiotic treatment contributes to gut microbiota dysbiosis. Previous studies have shown that fecal microbiota transplantation (FMT), fecal filtrate (FF), and activated charcoal (AC) treatments can prevent gut microbiota disturbances caused by antibiotics or Clostridioides difficile infection. However, these treatments have typically been limited to restoring gut microbiota after dysbiosis, and antibiotics must be discontinued beforehand. Here, we investigated the protective effects of these treatments on gut microbiota to prevent dysbiosis during concurrent systemic ceftriaxone administration. Methods: C57BL/6 mice that received intraperitoneal ceftriaxone for seven consecutive days were concomitantly treated with AC, FMT, FMT + AC, FF, or FF + AC via oral gavage. Gut microbiomes were analyzed using 16 S rRNA gene sequencing, and intestinal mucosal pathology was evaluated through H&E staining. Results: Systemic ceftriaxone administration significantly altered gut microbiota diversity and composition but did not affect intestinal mucosal histology. Alpha and beta diversity analyses showed that microbiota diversity decreased in all ceftriaxone-treated groups, with the ceftriaxone + FF + AC group retaining the highest diversity. The ceftriaxone + AC group had higher Enterococcus but lower Muribaculaceae relative abundances than the control (no ceftriaxone), ceftriaxone only, and ceftriaxone + FF + AC groups. Conclusions: These results show that fecal filtrate transplantation combined with activated charcoal treatment may help balance gut microbiota diversity and reduce the presence of resistant bacteria during ceftriaxone exposure.